2002
DOI: 10.21273/hortsci.37.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Crop Load Reduction and Fruit Size Following Multi-step Thinning of 'Empire' Apple

Abstract: Two years of field experiments were conducted in eastern New York to evaluate the efficacy of a multi-step thinning approach on reducing crop load (no. fruit per cm2 trunk cross-sectional area) and increasing fruit size of 'Empire' apple (Malus ×domestica Borkh.). Applications of Endothall (ET) at 80% bloom, NAA + carbaryl (CB) at petal fall (PF), and Accel™ + CB at 10 mm king fruitlet diameter (KFD), alone and in all combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…THINNING TREATMENTS. In 2002 and2003, water (C), 2% ammonium thiosulphate (ATS), a tank-mix of 2% fi sh oil + 2.5% lime sulphur (FOLS), and 3% vegetable oil emulsion (VOE) were each applied by air-blast sprayer at 200 gal/acre to heavily cropped 8and 9-year-old 'Bing'/'Gisela 5' sweet cherry canopies. Test trees were isolated by at least one untreated guard tree to the north and south.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…THINNING TREATMENTS. In 2002 and2003, water (C), 2% ammonium thiosulphate (ATS), a tank-mix of 2% fi sh oil + 2.5% lime sulphur (FOLS), and 3% vegetable oil emulsion (VOE) were each applied by air-blast sprayer at 200 gal/acre to heavily cropped 8and 9-year-old 'Bing'/'Gisela 5' sweet cherry canopies. Test trees were isolated by at least one untreated guard tree to the north and south.…”
Section: Methodsmentioning
confidence: 99%
“…fruit number per tree (i.e., cluster) is monitored often and modifi ed several times throughout a growing season and crop load management strategies are usually several-tiered. These may include a multiplicity of chemical blossom and postbloom thinners (Byers and Carbaugh, 1991;Dennis, 2000;Westwood, 1993), and hand thinning in the current season, as well as gibberellic acid to reduce (Bradley and Crane, 1959;Tromp, 1982), or ethephon or naphthaleneacetic acid (NAA) to increase, bloom density in the subsequent season (Byers, 1993;Stover et al, 2002). In contrast, crop load of many stone fruit species (Prunus L.) is reduced primarily by hand thinning, although research has shown potential for chemical thinning, especially for peach [P. persica (L.) Batsch.]…”
mentioning
confidence: 99%
“…Research was conducted on interactions between ET and postbloom compounds in multistep thinning programs (Bound and Wilson, 2007;Stover et al, 2002). While assessing a multistep thinning program, Stover et al (2002) observed that the addition of a petal fall thinning application was beneficial in a 2-year trial, but the addition of a blossom-thinning spray with ET was not. Despite a significant reduction in crop load, ET reduced fruit weight when compared with the control.…”
Section: Thinning Treatment Yxwmentioning
confidence: 99%
“…Additionally, abiotic factors such as solar radiation and temperature correlate to abscission rates (Lordan et al 2019). This variability necessitates a multistep thinning approach requiring multiple chemical thinner applications during the bloom and postbloom period (Stover et al 2002).…”
mentioning
confidence: 99%